Comparative study of bacteriology in recurrent tonsillitis among children and adults - Loganathan, A.; Arumainathan, U.D.; Raman, R. (Stamford Publishing Pte Ltd, 2006)
INTRODUCTION: Diagnosis and treatment of acute tonsillitis are one of the most common problems seen at an otorhinolaryngology clinic in both adult and paediatric populations. Much has been written about bacteriology of recurrent tonsillitis but it remains a controversial topic. Despite the fact that tonsillitis is so common, consensus seems to be lacking as to the main causative organism and the differences between children and adults. The tonsillar core bacteriology of 233 patients with recurrent tonsillitis who underwent tonsillectomy from January 2000 to June 2003 is presented.